Searching for the Yet-Nonexistent: Contemporary Kazakhstani Poetry and Kazakh Identity - Kazhyakpar, Aibarsha (Nazarbayev University School of Sciences and Humanities, 2020)
This project explores the narratives that contemporary Kazakhstani poets Ardak Nurgazy and Anuar Duisenbinov, who belong to two marginal groups of the society, build around the question of Kazakh national identity. In their poetry both poets use the notion of rebirth which can be found at the core of the most important national program of Kazakhstan “Rukhani Zhangyru” [Spiritual modernization/renewal]. However, the poets deconstruct that notion of rebirth and reveal the gap between today’s nation and its nomadic ancestors. Their lyrical heroes attempt to reconnect with the nation’s past by reestablishing their relationship with such historical and mythical figures like Korkyt, Kerei Khan, and Khoja Akhmed Yasawi. But the gap between them seems unsurmountable because the modern-day nation drastically differs from its ancestors: it is linguistically and culturally hybrid. This leaves the lyrical heroes feeling disoriented and unbelonging.
Keywords: Kazakh identity; hybridity; rebirth; ancestor figures; belonging; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics